2016
DOI: 10.1002/lsm.22542
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic effects of 10-HzPulsed wave lasers in rat depression model: A comparison between near-infrared and red wavelengths

Abstract: This study showed that non-invasive tLLLT using 10-Hz pulsed NIR laser light was as effective as Citalopram and more effective than red laser in the treatment of depressive-like behaviors and may help improve tLLLT as an alternative non-pharmacological treatments of psychological disorders such as depression. Lasers Surg. Med. 48:695-705, 2016. © 2016 Wiley Periodicals, Inc.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
37
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 47 publications
(39 citation statements)
references
References 80 publications
2
37
0
Order By: Relevance
“…Serum cortisol levels were significantly increased in mice underwent to CRS procedure that confirms the results of a previous depression study [31]. The effect of NIR (810 nm, 10 Hz) TPBM on cortisol levels in CMS rat model was examined by Salehpour et al [20] and no significant changes were observed in cortisol concentrations after TPBM. Probably, the delivered dose to the PFC (about 1.2 J/cm 2 ) was not sufficient to make a therapeutic effect.…”
Section: Discussionsupporting
confidence: 80%
See 2 more Smart Citations
“…Serum cortisol levels were significantly increased in mice underwent to CRS procedure that confirms the results of a previous depression study [31]. The effect of NIR (810 nm, 10 Hz) TPBM on cortisol levels in CMS rat model was examined by Salehpour et al [20] and no significant changes were observed in cortisol concentrations after TPBM. Probably, the delivered dose to the PFC (about 1.2 J/cm 2 ) was not sufficient to make a therapeutic effect.…”
Section: Discussionsupporting
confidence: 80%
“…These results are parallel to the prior depression studies [27,28]. In a study by Salehpour et al [20] the anti-anxiety effect of NIR (810 nm, 10 Hz) TPBM in CMS rat was evaluated by EPM test. In their study, a NIR dose of 1.2 J/cm 2 was delivered to the PFC and non-significant improvements in the both %OAE and %OAT variables were observed.…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…Recently, transcranial NIR PBM therapy has been suggested as a non-invasive neurostimulation modality in the central nervous system and is emerging as a novel promising treatment to defeat depression (Caldieraro et al, 2018; Cassano et al, 2015; Cassano et al, 2016; Salehpour and Rasta, 2017). Previous reports from our laboratory and others have shown that repeated delivery of NIR laser therapy produces an antidepressant-like effect in the FST (Mohammed, 2016; Salehpour et al, 2016; Wu et al, 2012; Xu, et al, 2017) and TST (Xu, et al, 2017). Nevertheless, in the current study, we showed that transcranial NIR PBM therapy for 5 days produced a notable antidepressant-like effect, as indicated by shorter immobility time in the FST and TST.…”
Section: Discussionmentioning
confidence: 74%
“…The thickness of media tunica was measured using Motic Images version 2.0 and light microscope. The stained sections were anonymously evaluated by a histologist, see also [27].…”
Section: Treatment Processmentioning
confidence: 99%